Emergent spacetime properties from entanglement - Colafrancheschi, Eugenia (2022)
The last century saw the development of two revolutionary theories: Einstein’s general relativity, which taught us that spacetime is a physical system, i.e. the gravitational field; and quantum mechanics, which revealed properties of microscopic systems foreign to the way we perceive reality in our everyday life, such as non-locality. We are now trying to reach a new turning point: the formulation of a theory of quantum gravity, capable of reconciling these revolutionary discoveries from microscopic to macroscopic scales, i.e. describing physical scenarios in which both gravity and quantum mechanics do enter, and matching validated theories for those where only one (or none) of the two does.